Effect of pH and protein-polysaccharide ratio on the intermolecular interactions between amaranth proteins and xanthan gum to produce electrostatic hydrogels. (August 2022) - Cortez-Trejo, M.C.; Figueroa-Cárdenas, J.D.; Quintanar-Guerrero, D.; Baigts-Allende, D.K.; Manríquez, J.; Mendoza, S.
Abstract: The development of new acid-induced mixed hydrogels based on amaranth proteins and xanthan gum is discussed. The influence of pH and protein-polysaccharide ratio on intermolecular interactions and gel properties was investigated. From a protein solubility assay and FTIR analyses, it was shown that while proteins form electrostatic hydrogels with xanthan gum at pH < pI (4.0), room temperature, and without the addition of crosslinking agents, at pH > pI (5.5) a higher incompatibility between charged biopolymers led to the formation of cross-linked soft hydrogels, promoted by hydrophobic interactions and to a lesser extent by electrostatic forces. Raman spectroscopy results, on the other hand, suggested there were no significant changes in the secondary structure of amaranth proteins. However, changes in their tertiary structure as a function of pH and ratio were evidenced. Regarding gel properties, the electrostatic hydrogels obtained at pH 4.0 showed more aggregated, denser, and stronger structures than gels prepared at pH 5.5. In addition, at both pH values, the increase of protein-polysaccharide ratio showed an adverse effect due to increased protein-protein associations. The overall results suggest that acidification of API:XG systems until pH 4.0 is a promising pathway for producing electrostatic hydrogels for food applications. Graphical abstract: Image 1 Highlights: Amaranth proteins-xanthan mixtures produced mixed hydrogels by slow acidification. Hydrogels were produced at room temperature and without crosslinking agents. At pH 4.0 (<pI), electrostatic hydrogels were obtained at ratios from 1:1 to 5:1. Electrostatic hydrogels showed the strongest and most aggregated networks. At pH 5.5 (>pI), soft and non-electrostatic hydrogels were reticulated.